Asparagus Officinalis: An Herbal Candidate for an Intraoral Healing Mouthwash: In-vitro healing effects of Asparagus officinalis - Shamsoddin, Erfan; Bashash, Davood; Zarei, Malek; Houshmand, Behzad (Journal of Dental School, 2021)
Objectives Asparagus officinalis (A. officinalis) extract has several bioactive ingredients. This study assessed the healing effects of A. officinalis methanolic extract. Methods In this experimental study, after preparing the methanolic extract of A. officinalis with a concentration of 100 , its bioactive ingredients were determined using high-performance liquid chromatography (HPLC) and then its cytotoxicity was assessed using the methyl thiazolyl tetrazolium (MTT) assay. Five experimental groups with 25 samples were assessed as follows: (I)human gingival fibroblast(HGFs) cultured in high-glucose Dulbecco’s modified Eagle’s medium (DMEM), (II) same as group Ibut with 10 μg/mL methanolic extract of A. officinalis, (III) same as group Ibut with 25μg/mL methanolic extract of A. officinalis, (IV) same as group Ibut with 50 μg/mL methanolic extract of A. officinalis, and (V)same as group Ibut with 100μg/mL methanolic extract of A. officinalis. Cell motility in the control group and group Vwas examined quantitatively using the cell scratch assay at 24 h. We used one-way ANOVA and t-test to analyzethe cytotoxicity of A. officinalis extract and the motility of HGFs, respectively. Results The MTT assay showed no significant difference in cell viability among the experimental groups (P=0.07). A remarkable cellular wound closure equal to 60.85% was noted after 24 h. Conclusion The methanolic extract of A. officinalis with a concentration of 100 μg⁄mL showed significant healing effects on an experimental scratch setup of HGFs.